(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Brightened metallic nanoparticles serve to catalyse chemical processes that hold significant implications for both industrial applications and societal advancement. The utilization of light in chemical reactions presents an intriguing replacement to petroleum, considering its prevalence as a sustainable energy medium. Light facilitates the unlocking of electronic improvements to chemical reactions by generating and activating hot carriers on molecular adsorbates, a process not accessible through conventional thermochemical conversions. This Perspective aims to offer a comprehensive overview of significant techniques and findings from many years of surface research in science that have established the groundwork for contemporary investigations into hot carrier photochemistry. Recent developments in nanoscience and heterogeneous catalysis have led to the emergence of novel materials, especially metal nanoparticles that maintain collective electronic oscillations when exposed to light (plasmon resonances), which can be utilized as effective photo-catalysts. Plasmonic photo-catalysts exhibit significant optical absorption and can be meticulously engineered via Landau damping to optimize hot carrier generation within a specified volume, thereby enhancing their application in relevant reactions. Photo Chemistry holds significant importance in numerous facets of this research domain. This tool serves a distinctive purpose in the synthesis of metal nanoparticles and plays a crucial role in exploring the underlying mechanisms of their formation.